2018 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) 2018
DOI: 10.1109/vlhcc.2018.8506573
|View full text |Cite
|
Sign up to set email alerts
|

End-User Development in Social Psychology Research: Factors for Adoption

Abstract: Psychology researchers employ the Experience Sampling Method (ESM) to capture thoughts and behaviours of participants within their everyday lives. Smartphone-based ESM apps are increasingly used in such research. However, the diversity of researchers' app requirements, coupled with cost and complexity of their implementation, has prompted end-user development (EUD) approaches. In addition, limited evaluation of such environments beyond lab-based usability studies precludes discovery of factors pertaining to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Our previous work described Jeeves in relation to EUD adoption requirements for psychology researchers [21], as well as how usability issues in a lab study of Jeeves were almost entirely separate to real-world usability challenges identified in case studies [22]. In this work, we extend on both of these results by triangulating interview feedback with analysis of our case studies.…”
Section: The Jeeves Eud-esm Toolmentioning
confidence: 74%
See 1 more Smart Citation
“…Our previous work described Jeeves in relation to EUD adoption requirements for psychology researchers [21], as well as how usability issues in a lab study of Jeeves were almost entirely separate to real-world usability challenges identified in case studies [22]. In this work, we extend on both of these results by triangulating interview feedback with analysis of our case studies.…”
Section: The Jeeves Eud-esm Toolmentioning
confidence: 74%
“…In response, we have developed the Jeeves tool to allow end-users with no programming skills to create their own ESM apps, couple them to participants' smartphones, and receive assessment results in real-time. While our previous work has addressed design decisions and lab-based usability studies of Jeeves [20,22], this paper extends the evaluation conducted in [21] to synthesise necessary functionality and constraints of EUD for ESM apps (hereby referred to as EUD-ESM) addressing the following question:…”
Section: Introductionmentioning
confidence: 99%
“…Recent additions to the library of Jeeves blocks include participant "attribute" blocks, akin to programmatic variables, conditional statement blocks, and context-sensitive triggers. These extensions were derived from a review of literature detailing the potential benefits of modern smartphone ESM, and were positively received by interviewed psychology researchers [20]. However, the researchers who were interviewed did not actually use Jeeves.…”
Section: Related Workmentioning
confidence: 99%
“…Nielsen's guidelines on designing study tasks were followed closely, by ensuring that participants were not primed with the trigger-action terminology of Jeeves [16]. The tasks were intended to address updated functions of Jeeves that were perceived as useful for researchers to create personalised ESM study specifications [20] -primarily the use of "attribute" blocks to represent variables, as well as conditional statements. Note that the hypothetical app end-users are referred to in study tasks as patients rather than participants, to distinguish them from the participants in this study.…”
Section: Tasksmentioning
confidence: 99%